The war in Korea - Leckie, Robert (New York: Random House, 1963)
Este texto contiene los siguientes temas: The U. N. Wins its first battle, How the wars began, The fall of seoul, Enter the United Nations, Enter the Americans, General Dean's Last Stand, Bulldog Walker at Pusan, The Glory og MacArthur, The Chinese Trap, The secodn retreat from seoul, The road back, The true talks drag on, The fighting ends
Keywords: Korea